Place-based decarbonisation in low and middle income countries: a whole systems view - Balta-Ozkan, Nazmiye; Dalkmann, Holgar (Elsevier, 2024)
Decarbonisation of transport is essential to the efforts to limit global temperature increase to under 1.5 °C as agreed in the Paris Agreement. According to the International Energy Agency (IEA), global emissions from transport were around 8 gigatonnes (Gt) in 2022 – an increase of three percent against the previous year (IEA, 2023). This sets a stark contrast against the annual 3% reduction target that is needed to be on track with IEA's Net Zero Emissions by 2050 (NZE) scenario. This is a significant challenge as transport emissions were increasing 1.7% per annum in the last 30 years, driven by a very strong demand for transport in emerging markets and developing economies. The latest Stocktake by the UNFCCC in September 2023 flags that the combined pledges of the 193 Parties under the Paris Agreement would put the world on track for around 2.5. Degrees Celsius by 2030 (UNFCCC Secretariat, 2023). In 2021, 98% of the National Determined Contribution (NDCs) mentioned transport, but only 83% included transport measures and only 18% set specific CO2 reduction targets for the sector (ITF, 2023).